2019
DOI: 10.15356/2076-6734-2019-4-421
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of soil temperatur on permafrost in natural and anthropogenic disturbed conditions in the Tunkinskaya Depression

Abstract: The territory of the study is the Tunkinsky intermountain basin (South-Western Baikal region, Republic of Buryatia) which belongs to the area of sporadic (island) distribution of permafrost. Soil temperature controls many biotic and abiotic processes in it, so it is important to monitor the freezing and thawing regimes in peat and mineral soils. The object of the study is coarse-humic cryogenic soils on sandy lacustrine-alluvial sediments. The first site was represented by natural coarse-humic cryogenic soils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…The temperature in the topsoil, rather than in the air, ultimately determines the distribution and productivity of most terrestrial species, as well as many ecosystem functions at or below the soil surface [33][34][35][36]. Voropay et al [2] demonstrated that changes in vegetation cover caused by anthropogenic factors, as well as changes in soil moisture, its morphological structure and granulometric composition of the upper layer, lead to a change in the temperature regime of permafrost and its degradation with decreasing its upper limit. The soil under the fallow warms up better and cools down faster than under the spruce forest.…”
Section: Assessment Of Soil Temperature As An Important Environment-f...mentioning
confidence: 99%
See 2 more Smart Citations
“…The temperature in the topsoil, rather than in the air, ultimately determines the distribution and productivity of most terrestrial species, as well as many ecosystem functions at or below the soil surface [33][34][35][36]. Voropay et al [2] demonstrated that changes in vegetation cover caused by anthropogenic factors, as well as changes in soil moisture, its morphological structure and granulometric composition of the upper layer, lead to a change in the temperature regime of permafrost and its degradation with decreasing its upper limit. The soil under the fallow warms up better and cools down faster than under the spruce forest.…”
Section: Assessment Of Soil Temperature As An Important Environment-f...mentioning
confidence: 99%
“…Most of the known global maps of soil temperature have been prepared on the basis of instrumental field-based observations [2,30,31,44,45]. At the same time, the use of remote sensing data allows a more detailed analysis of the HF distribution pattern.…”
Section: Mapping Using Space Imagesmentioning
confidence: 99%
See 1 more Smart Citation